Changes in the Morphology of Hypoglossal Motor Neurons in the Brainstem of Developing Rats. Issue 6 (13th November 2018) - Williams, Paul Allen; Bellinger, Denise L.; Wilson, Christopher G.
ABSTRACT: The autonomic brainstem generates breathing rhythm by integrating inputs from chemosensors and mechanosensors in the viscera and coordinating descending outputs from higher structures in the central nervous system. Hypoglossal motoneurons (XII MNs) receive inputs from respiratory premotor neurons, important for maintaining airway patency. Previous studies in rodents report significant changes in breathing control during the first 3 weeks of life, with a sensitive period at 10 to 13 days postbirth (P10–P13) characterized by pronounced changes in neurotransmitters, excitation‐inhibition balance, and breathing physiology. However, age‐dependent morphological changes of XII MNs during the first 3 weeks postbirth and especially this sensitive period are under‐studied. Here, we comprehensively characterize and quantify the early morphological changes in rat XII MNs. We hypothesized that morphological changes in XII MNs correspond to the functionally defined sensitive period observed at postnatal day 10–13 (P10–P13). To test this hypothesis, we used an innovative contemporary statistical approach to analyze Golgi‐Cox stained XII MNs at nine postnatal ages between P1 and P21. Our findings reveal two subpopulations of XII MNs, which are dependent on age and morphological features. Soma size increased approximately 40% from P1 to P21, without changing shape. However, dendritic arborization increased in extent/distance and complexity. Dendritic branching of developing neurons significantly increased from P1 through P13, with the greatest increase at P10–P13 based on the Sholl method. Our detailed characterization of XII MN morphological development establishes a foundation for the study and elucidation of morphological changes caused by maternal and perinatal conditions. Anat Rec, 302:869–892, 2019. © 2018 Wiley Periodicals, Inc.